Lexical Planning in People Who Stutter: A Defect in Lexical Encoding or the Planning Scope? - Zhao, Liming; Lian, Miaoqing (Frontiers in Psychology, 2021)
Developmental stuttering is a speech fluency disorder which is widely discussed. Research on its mechanism has focused on an atypical interface between planning (PLAN) and execution (EX) processes, called EXPLAN model. However, it remains unclear what cause this atypical interface for persons who stutter. A straightforward assumption is that stuttering speakers adopt a smaller scope of speech planning, while a defect in word retrieval can be a confounding. To shed light on this issue, the present research took the semantic blocking effect as an index to examine the lexical planning in word and phrase productions. In Experiment 1 for word production, pictures from the same semantic category were combined to form homogeneous blocks, and pictures from different categories respectively were combined to form heterogeneous blocks. A typical effect of semantic blocking, showing longer naming latencies for homogeneous blocks than heterogeneous ones, was observed both for stuttering and fluent speakers. However, this effect was smaller for stuttering speakers, which is object to lexical defect in stuttering. In Experiment 2 for a conjoined noun phrase production task, the pictures referring to the first noun was manipulated into homogeneous and heterogeneous conditions. The semantic blocking effect was also much smaller for stuttering speakers, indicating a smaller scope of lexical planning. The findings therefore provide more evidence for the EXPLAN model, and reveal that a smaller scope of lexical planning rather than lexical defect causes the atypical interface for stuttering. A comparison between these two tasks showed some implication for syntactic defect in stuttering.